Moon boy. Vol. 3 - Yi, Yŏng-yu (Ice Kunion, 2006)
Myung-Ee, determined to protect Yu-Da from the hungry foxes, has a real fight with the Fox Tribe. But, she encounters the "Black" Yu-Da instead of the Yu-Da she knows. Has his memory returned or has be been faking?